Underlying Kidney Diseases and Complications for COVID-19: A Review - Prince Dadson; Comfort Dede Tetteh; Eleni Rebelos; Robert M. Badeau; Dariusz Moczulski (FRONTIERS MEDIA SA, 2022)
There is mounting evidence supporting that patients with kidney diseases are particularly vulnerable to coronavirus disease-2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The review was conducted to examine the risk and complications of COVID-19 among patients with confirmed cases of underlying kidney disease. A search of Google Scholar, PubMed and Science direct databases to August 2020 was conducted using search terms pertaining to kidney diseases, renal insufficiency, kidney injury, angiotensin receptors, hemodialysis, and kidney transplant. We briefly reviewed COVID-19 in the context of kidney diseases. A significant proportion of hospitalized patients for COVID-19 have acute kidney injury, which further deteriorates their prognosis. COVID-19 increases morbidity and mortality among people already diagnosed with kidney disorders and obesity due to multiple organ injury caused by the SARS-CoV-2. This review supports the need for clinicians to carefully manage and monitor all patients with renal disorders in order to minimize acute kidney injuries. Although some therapeutic drugs have been suggested by some studies, treatment should be administered cautiously not to worsen the condition of the kidney. Further studies are required to highlight the efficient management of patients with underlying kidney diseases, who are infected with SARS-CoV-2. With proactive systematic screening and triaging, close monitoring and prompt management of coexisting other infections, the COVID-19 disease burden among these patients could be reduced.